A new species of Amolops (Anura: Ranidae) from China, with taxonomic comments on A. liangshanensis and Chinese populations of A. marmoratus - Lyu, Zhi-Tong; Zeng, Zhao-Chi; Wan, Han; Yang, Jian-Huan; Li, Yu-Long; Pang, Hong; Wang, Ying-Yong (Zootaxa, 2019)
Amolops shuichengicus sp. nov., a new species of the A. mantzorum group is described from Guizhou, southwest China, on the basis of significant molecular divergences in 16S + CO1 genes and the combination of morphological characteristics: small body size, SVL 34.6–39.6 mm in adult males and 48.5–55.5 mm in adult females; dorsal skin relatively smooth; presence of vomerine teeth; presence of cream maxillary gland from lower edge of eye to the anterior of supratympanic fold; presence of supratympanic folds and glandular dorsolateral folds; tympanum indistinct; absence of a circummarginal groove on the disk of the first finger; presence of supernumerary tubercles below the base of fingers III and IV; absence of outer metatarsal tubercle and tarsal glands; males without vocal sacs. In addition, evidenced by the phylogenetic analyses in this study and literature data, we suggest that A. liangshanensis should be synonymized with A. loloensis and the records of A. marmoratus in Yunnan, China should be referred to A. afghanus. Following our proposal, the genus Amolops contains 57 species, with 32 recorded from China.